Formazanate Complexes of Hypervalent Group 14 Elements as Precursors to Electronically Stabilized Radicals. (29th June 2018) - Maar, Ryan R.; Catingan, Sara D.; Staroverov, Viktor N.; Gilroy, Joe B.
Abstract: The stability of molecular radicals containing main‐group elements usually hinges on the presence of bulky substituents that shield the reactive radical center. We describe a family of Group 14 formazanate complexes whose chemical reduction allows access to radicals that are stabilized instead by geometric and electron‐delocalization effects, specifically by the square‐pyramidal coordination geometry adopted by the Group 14 atom (Si, Ge, Sn) within the framework of the heteroatom‐rich formazanate ligands. The reduction potentials of the Si, Ge, and Sn complexes as determined by cyclic voltammetry become more negative in that order. Examination of the solid‐state structures of these complexes suggested that their electron‐accepting ability decreases with increasing size of the Group 14 atom because a larger central atom increases the nonplanarity of the ligand‐based conjugated π‐electron system of the complex. The experimental findings were supported by density‐functional calculations on the parent complexes and the corresponding radical anions.